If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = 81(x + 3) Reorder the terms: 9x = 81(3 + x) 9x = (3 * 81 + x * 81) 9x = (243 + 81x) Solving 9x = 243 + 81x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-81x' to each side of the equation. 9x + -81x = 243 + 81x + -81x Combine like terms: 9x + -81x = -72x -72x = 243 + 81x + -81x Combine like terms: 81x + -81x = 0 -72x = 243 + 0 -72x = 243 Divide each side by '-72'. x = -3.375 Simplifying x = -3.375
| 2(8x^2-25x-28)= | | -8+6x+3x=64 | | 5m-3Q=2+w(4Q-7m)forQ | | 9x-6(3-x)=3(x+6) | | 16=7(a-3)-12 | | -35=-5(m-3) | | 4x^2-18x+19=0 | | 1+5e+2e=78 | | 8x+2(x-4)=3(x+1)-2 | | -6(a-3)=24 | | 3x+5=3(x+3) | | 20=-16t(t-3) | | -3x-5(-x-4)=2 | | -5(y+2)=10 | | -1-7x+6x=-1 | | 4x+6y=103x+7y=12.5 | | 6(7x-1)=42x-6 | | 5(x+2)=-7x | | sqrt(-6y+37)=y-5 | | z=20x+6y | | 4y+9=z | | 3n-5=3n | | (3x^2-20x-7)=0 | | -3x-4x-6=-61 | | sin(x)=0.8191 | | 37=-7x+2(5x+2) | | 3log(4x)2=10 | | x^4+x^3+4x^2-24x-72=0factor | | x^4+x^3+4x^2-24x-72=0 | | factorx^4+x^3+4x^2-24x-72=0 | | 3(2x+5)+14=4(3x-7)-3 | | 7x=41 |